Observation of Damage of Cotton Fiber in the Processes of Blowing, Cleaning and Carding - Tojimirzaev Sanjar (EDP Sciences, 2021)
The quality of the produced yarn mainly depends on the properties of the raw material, its preparation for spinning, the condition of the equipment, and the preservation of the natural quality of cotton fiber during processing. The question of the number of defects in cotton fiber and their total content is a very important issue for cotton spinning. The non-standardized number of defects in the raw material reduces the quality indicators and yarn yield, which requires additional technological processes; therefore, on the part of production, the requirements for reducing the share of cotton fiber defects are constantly increasing. During processing in blowing and cleaning units and on carding machines, the cotton fiber is mechanically damaged. To observation the damaged fibers, we used the Congo-Roth red paint according to the method of Ch. Dore. Despite the carding is considered the last stage in the process of cleaning the fibers from impurities and defects in the spinning system, 30% of impurities and fiber defects still remain on the card sliver. Besides, it should be noted the carding machine is also considered an additional occurrence of defects, in particular (neps), which reduce the quality indicators of the card sliver and the finished product.